Development of the Centrifugal Blood Pump for a Hybrid Continuous Flow Pediatric Total Artificial Heart: Model, Make, Measure - Fox, Carson S.; Palazzolo, Thomas; Hirschhorn, Matthew; Stevens, Randy M.; Rossano, Joseph; Day, Steven W.; Tchantchaleishvili, Vakhtang; Throckmorton, Amy L. (Frontiers in Cardiovascular Medicine, 2022)
Clinically-available blood pumps and total artificial hearts for pediatric patients continue to lag well behind those developed for adults. We are developing a hybrid, continuous-flow, magnetically levitated, pediatric total artificial heart (TAH). The hybrid TAH design integrates both an axial and centrifugal blood pump within a single, compact housing. The centrifugal pump rotates around the separate axial pump domain, and both impellers rotate around a common central axis. Here, we concentrate our development effort on the centrifugal blood pump by performing computational fluid dynamics (CFD) analysis of the blood flow through the pump. We also conducted transient CFD analyses (quasi-steady and transient rotational sliding interfaces) to assess the pump’s dynamic performance conditions. Through modeling, we estimated the pressure generation, scalar stress levels, and fluid forces exerted on the magnetically levitated impellers. To further the development of the centrifugal pump, we also built magnetically-supported prototypes and tested these in an in vitro hydraulic flow loop and via 4-hour blood bag hemolytic studies (n=6) using bovine blood. The magnetically levitated centrifugal prototype delivered 0-6.75 L/min at 0-182 mmHg for 2,750-4,250 RPM. Computations predicted lower pressure-flow performance results than measured by testing; axial and radial fluid forces were found to be less than 3 N, and mechanical power usage was predicted to be less than 5 Watts. Blood damage indices (power law weighted exposure time and scalar stress) were less than 2%. All data trends followed expectations for centrifugal pump designs. Six peaks in the pressure rise were observed in the quasi-steady and transient simulations, correlating to the blade passage frequency of the 6-bladed impeller. The average N.I.H value (n=6) was determined to be 0.09 +/- 0.02 g/100L, which is higher than desired and must be addressed through design improvement. These data serve as a strong foundation to build upon in the next development phase, whereby we will integrate the axial flow pump component.